2017
DOI: 10.3390/ijms18010135
|View full text |Cite
|
Sign up to set email alerts
|

Treating the Synapse in Major Psychiatric Disorders: The Role of Postsynaptic Density Network in Dopamine-Glutamate Interplay and Psychopharmacologic Drugs Molecular Actions

Abstract: Dopamine-glutamate interplay dysfunctions have been suggested as pathophysiological key determinants of major psychotic disorders, above all schizophrenia and mood disorders. For the most part, synaptic interactions between dopamine and glutamate signaling pathways take part in the postsynaptic density, a specialized ultrastructure localized under the membrane of glutamatergic excitatory synapses. Multiple proteins, with the role of adaptors, regulators, effectors, and scaffolds compose the postsynaptic densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 174 publications
0
52
0
Order By: Relevance
“…The density of dendritic spines and the diameter of the spine head were significantly reduced in the MSNs of Het mice (Figure b,c). The level of postsynaptic density 95 (PSD95), a postsynaptic scaffold protein for excitatory synapses (Tomasetti et al, ), was reduced in Het mice compared to that in WT mice (Figure d). Together, defects in dendritic arbors, spines and postsynaptic density protein in the MSNs of Het mice suggest impaired glutamatergic synaptic transmission in the striatal neural network.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The density of dendritic spines and the diameter of the spine head were significantly reduced in the MSNs of Het mice (Figure b,c). The level of postsynaptic density 95 (PSD95), a postsynaptic scaffold protein for excitatory synapses (Tomasetti et al, ), was reduced in Het mice compared to that in WT mice (Figure d). Together, defects in dendritic arbors, spines and postsynaptic density protein in the MSNs of Het mice suggest impaired glutamatergic synaptic transmission in the striatal neural network.…”
Section: Resultsmentioning
confidence: 98%
“…The density of dendritic spines and the diameter of the spine head were significantly reduced in the MSNs of Het mice (Figure 7b,c). The level of postsynaptic density 95 (PSD95), a postsynaptic scaffold protein for excitatory synapses (Tomasetti et al, 2017), was reduced in Het mice compared to that in WT mice (Figure 7d).…”
Section: Morphological Changes In Striatal Median Spiny Neurons In mentioning
confidence: 99%
“…Proteomic and genomic analyses of synapses in human brain samples from controls or individuals with schizophrenia found altered expression of multiple proteins with known specific roles in NMDA function. 15,16 Although the proportion of individuals with schizophrenia in this subtype is not known, the NMDAR-related molecules are well represented in the identified risk genes. 15,16 The serine racemase (SR) gene is one of several risk genes for schizophrenia that affect NMDAR function and its downstream signaling.…”
mentioning
confidence: 99%
“…Early work suggested that the similar effects were not obtained in other brain regions (Huang & Kandel, 1995;Law-Tho, Hirsch, & Crepel, 1994). Recent studies have found that other brain regions do express a synergy between dopamine and glutamate receptor and greater details have uncovered the molecular foundation for these interactions (Sarantis, Matsokis, & Angelatou, 2009;Tomasetti et al, 2017). There are both similarities and differences obtained for DA-glutamate interaction making neostriatal modulation distinctive and an influence from the internal, local neural connectivity in each brain region important (Sesack, Carr, Omelchenko, & Pinto, 2003).…”
Section: Dopamine-g Lutamate Inter Ac Ti On S: P Oss Ib Le Influen mentioning
confidence: 99%
“…The next step was to examine whether this differential modulation also applies to components of synaptic responses evoked by electrical stimulation of neostriatal afferents and mediated by activation of specific subtypes of EAA receptors (Levine, Li, Cepeda, Cromwell & Altemus, 1996). Recent studies have found that other brain regions do express a synergy between dopamine and glutamate receptor and greater details have uncovered the molecular foundation for these interactions (Sarantis, Matsokis, & Angelatou, 2009;Tomasetti et al, 2017). The specific subtype of EAA receptor activated was crucial to the direction of effect.…”
Section: Dopamine-g Lutamate Inter Ac Ti On S: P Oss Ib Le Influen mentioning
confidence: 99%